Visual and graphic features of the Russian language edition of Phil O'Neill's book "Poems from the unconscious" as the literature of trauma - Bliznetsov Daniil M.; Rodina Inna V. (Архитектон)
The Russian edition project of Phil O'Neill's book "Poems from the Unconscious" is described as a literature of trauma from the perspective of its visual and graphic features. The illustrations and typography of various books related to the literature of trauma are analyzed in order to identify common features in their artistic design and justify the choice of visual and graphic means for the translated edition.